PENGEMBANGAN E-MODUL MATEMATIKA FLIPBOOK KELAS V SD MENGGUNAKAN PENDEKATAN PROBLEM BASED LEARNING DAN INTEGRASI COMPUTATIONAL THINKING PADA MATERI OPERASI PENJUMLAHAN DAN PENGURANGAN PECAHAN KELAS V SD - Neca Naula; Eka Sastrawati; Violita Zahyuni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Education plays a crucial role in determining a nation's progress. Mathematics is a strategic subject in elementary education because it can develop students' logical, analytical, creative, and critical thinking skills. One important topic in fifth grade is the addition and subtraction of fractions. This topic often presents difficulties because learning still emphasizes mechanical procedures, resulting in students lacking a deep understanding of the concept and having difficulty solving problems reflectively. This study aims to develop a Mathematics Flipbook E-Module based on Problem Based Learning integrated with Computational Thinking to improve students' understanding of fraction concepts and reflective thinking skills. The study used the Research and Development (R&D) method with the DDD-E (Decide, Design, Develop, Evaluate) model. The research stages included needs analysis, interactive content design, digital media development, and validity and practicality evaluation through limited and large-scale trials. The results showed that the developed Flipbook E-Module was valid according to material and media experts. This product was practical for use by teachers and students. The E-Module was proven to increase learning motivation, critical thinking skills, and systematic fraction problem-solving skills. The integration of interactive digital media, problem-based learning, and computational thinking supports deeper and more contextual mathematics learning in accordance with the Independent Curriculum. This product serves as both teaching materials and learning tools that encourage students to think creatively, critically, reflectively, and systematically.